2019
DOI: 10.3390/biom9110675
|View full text |Cite
|
Sign up to set email alerts
|

The Lysosomal Sequestration of Tyrosine Kinase Inhibitors and Drug Resistance

Abstract: The Lysosomal sequestration of weak-base anticancer drugs is one putative mechanism for resistance to chemotherapy but it has never been directly proven. We addressed the question of whether the lysosomal sequestration of tyrosine kinase inhibitors (TKIs) itself contributes to the drug resistance in vitro. Our analysis indicates that lysosomal sequestration of an anticancer drug can significantly reduce the concentration at target sites, only when it simultaneously decreases its extracellular concentration due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 34 publications
(60 reference statements)
0
14
0
Order By: Relevance
“…Lysosomes have been observed as a drug sink for many lysosomotropic agents, including many prescribed drugs like doxorubicin, vinblastine, imipramine, and a variety of TKIs, like gefitinib (Skoupa et al, 2020), imatinib (Burger et al, 2015), and sunitinib (Ruzickova et al, 2019). In a recent study by Ruzickova et al the lysosomotropic agent sunitinib was shown to be capable of increasing overall lysosomal sequestration of the TKIs tested, although this effect was insufficient in reducing sensitivity to the TKIs by the hypothesized mechanism of sequestering them away from their mechanistic target sites as the concentrations tested in culture maintained a static extracellular concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lysosomes have been observed as a drug sink for many lysosomotropic agents, including many prescribed drugs like doxorubicin, vinblastine, imipramine, and a variety of TKIs, like gefitinib (Skoupa et al, 2020), imatinib (Burger et al, 2015), and sunitinib (Ruzickova et al, 2019). In a recent study by Ruzickova et al the lysosomotropic agent sunitinib was shown to be capable of increasing overall lysosomal sequestration of the TKIs tested, although this effect was insufficient in reducing sensitivity to the TKIs by the hypothesized mechanism of sequestering them away from their mechanistic target sites as the concentrations tested in culture maintained a static extracellular concentration.…”
Section: Discussionmentioning
confidence: 99%
“…2C). Recent reports suggest that many weakly basic lipophilic compounds, including CQ, activate lysosomal biogenesis by activating the transcription factor EB (TFEB) (Lu et al, 2017;Zhitomirsky et al, 2018;Zhao et al, 2020), which ultimately increases the lysosomal volume fraction of treated cells and should allow them to sequester even more drug than their original baseline (Ruzickova et al, 2019). CQ has been observed to activate TFEB and increase lysosomal content of the cell, so we investigated the capability of HCQ to do the same.…”
Section: Hcq Increases the Size Of The Lysosomal Compartmentmentioning
confidence: 99%
“…However, it is probably not a universal mechanism that occurs in all types of cancer cells. In our laboratory, we have recently shown that A549, MCF7 and K562 tumor lines exposed to non-toxic sunitinib concentrations for three days, increased significantly their ability to sequester various TKIs by lysosomes without observable lysosomal biogenesis [31].…”
Section: Discussionmentioning
confidence: 98%
“…Absolute accumulation of TKIs in lysosomes was calculated as described previously [30,31]. Briefly, the value of intracellular accumulation of particular TKI in the presence of BafA1 was subtracted from the value of intracellular accumulation of particular TKI in the absence of BafA1.…”
Section: Calculation Of Tkis In Lysosomesmentioning
confidence: 99%
See 1 more Smart Citation